BRD3 and BRD4 BET Bromodomain Proteins Differentially Regulate Skeletal Myogenesis - Thomas C. Roberts; Usue Etxaniz; Alessandra Dall’Agnese; Shwu-Yuan Wu; Cheng-Ming Chiang; Paul E. Brennan; Matthew J. A. Wood; Prem Puri (2017)
Myogenic differentiation proceeds through a highly coordinated cascade of gene activation that necessitates epigenomic changes in chromatin structure. Using a screen of small molecule epigenetic probes we identified three compounds which inhibited myogenic differentiation in C2C12 myoblasts; (+)-JQ1, PFI-1, and Bromosporine. These molecules target Bromodomain and Extra Terminal domain (BET) proteins, which are epigenetic readers of acetylated histone lysine tail residues. BETi-mediated anti-myogenic effects were also observed in a model of MYOD1-mediated myogenic conversion of human fibroblasts, and in primary mouse and human myoblasts. All three BET proteins BRD2, BRD3 and BRD4 exhibited distinct and dynamic patterns of protein expression over the course of differentiation without concomitant changes in mRNA levels, suggesting that BET proteins are regulated at the post-transcriptional level. Specific BET protein knockdown by RNA interference revealed that BRD4 was required for myogenic differentiation, whereas BRD3 down-regulation resulted in enhanced myogenic differentiation. ChIP experiments revealed a preferential binding of BRD4 to the Myog promoter during C2C12 myoblast differentiation, co-incident with increased levels of H3K27 acetylation. These results have identified an essential role for BET proteins in the regulation of skeletal myogenesis, and assign distinct functions to BRD3 and BRD4.